Teaching empathy to medical students. (22nd December 2022) - McNally, Gemma; Haque, Enam; Sharp, Sarah; Thampy, Harish
Abstract: Background: Empathy is a core skill essential to patient‐centred care. Yet a decline in empathy throughout undergraduate medical education is well recognised. The mainstay of existing teaching approaches to foster medical students' empathic ability has largely focused on the cognitive domain of empathy within the context of communication skills learning. However, there is growing evidence for educational initiatives that better evoke students' affective emotional responses. Approach: A student‐led educational initiative was created to enhance medical students' understanding of empathy through undertaking different experiential approaches. Eight medical students were invited to participate in an empathy workshop that involved two experiential approaches: personal simulation, and patient narrative, selected given their expected focus on the affective domain. Evaluation: A subsequent focus group discussion explored students' reactions, learning, and intended future change in practice. Discussions were coded and analysed for descriptive themes. Both initiatives were reported to generate students' empathic responses. Personal simulation evoked more affective domains whilst patient narratives additionally created cognitive empathic insight into the impact of the patient's condition. Students also reported intended changes to their future consulting practices. Conclusions: Although this is a small‐scale exploration of medical students' experiences of empathy‐related teaching initiatives, it offers insight into how each initiative could target different aspects of empathy. Data support the use of even brief experiential teaching to improve medical students' empathy during their undergraduate training. We provide recommendations for clinical educators who are considering designing similar initiatives within their undergraduate medical curricula.